Vanuatu Early Childhood Development : SABER Country Report 2012 - World Bank (Washington, DC, 2014)
This report presents an analysis of the Early Childhood Development (ECD) programs and policies that affect young children in Vanuatu. This report is part of a series of reports prepared by the World Bank using the SABER-ECD framework1 and includes analysis of early learning, health, nutrition and social and child protection policies and interventions in Vanuatu, along with regional and international comparisons.